PENGARUH LOKASI, KUALITAS PELAYANANDAN KEPUASAN PELANGGAN TERHADAP SWITCHING INTENTION PADA “WISMA SADEWA”PANGENREJO PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
This research aims to test the determinants of location, service quality and customer satisfaction regarding switching intention at "Wisma Sadewa" Pangenrejo, Purworejo. Data collection techniques in this research were obtained by observation, interviews, questionnaires, documentation and literature study. The sampling technique used was a saturated sample of 16 people. The research methods in this research were multiple correlation analysis, multiple regression, t test and determination test. The results of multiple regression testing obtained the equation Y=3.355+0.950X1+0.549X2+0.117X3. Adjusted R Square is 0.908, this number is called the coefficient of determination value. The determination value is 0.908 or 90.8%. Based on the level of significance, α=0.05 with a confidence level of 95% with ttabel =n-k-1, it is obtained that ttabel is 1,796, while the calculation results produce fhitung Location variable (X1) of 3.22 2 So the value of fhitung is greater than the value of ttabel (3,222 >1.796) or a sig value of 0.007 (P<0.05), so that the Location variable (X1) has a positive and significant effect on Switching Intention (Y). ttabel (1.886 >1.796) or a sig value of 0.030 (P<0.05), so that the service quality variable (X2) has a positive and significant effect on Switching Intention (Y). ttabel (0.619 <1.796) or a sig value of 0.548 (P>0.05), so that the customer satisfaction variable (X3) does not have a positive and significant effect on Switching Intention (Y). Based on the SPSS output results above, with a level of significance, α = 0.05 with a confidence level of 95% with fhitung =n-k-1, it is obtained that ftabel is 2,328, while the calculation results based on table 4.32 which are carried out produce fhitung The variable location, service quality and customer satisfaction is 50,399. So the value of fhitung is greater than the value of ftabel (50,399 > 2,328) or a sig value of 0.00 (P<0.05), so that the variables Location, Service Quality and Customer Satisfaction have a positive and significant influence on the Switching Intention (Y) decision. Based on the results The research conducted by the author provides suggestions for Wisma Sadewa continues to improve the quality of facilities and infrastructure as well as providing supporting services including technicians, cleaning staff and security staff to support customer satisfaction.